Music Analysis and the Social Life of Jazz Recordings - Butterfield, Matthew W. (Current Musicology, 2001)
In recent years, music theorists have taken an increased interest in jazz and produced more and more analytical studies of improvised jazz solos. For many involved in jazz research, this has been an encouraging sign. Most obviously, it has signaled the respectability jazz has attained within the musicological disciplines since the mid-1980s as a music worthy of detailed criticism. It has also expanded the range and depth of jazz scholarship, providing new points of entry into the field for emerging scholars who may otherwise have pursued a different course. More importantly, however, the growing sophistication of contemporary analytical methods has enriched our understanding of the nature of jazz improvisation, enabling us to ask better questions about the music than in the past.